Metabolomics Reveals Specific Metabolic Changes in Sweet Cherries (Prunus avium L.) Subjected to Postharvest Treatment with Melatonin after Mechanical Stress - Ignacia Hernández; Excequel Ponce; Juan Vidal; Rosana Chirinos; David Campos; Romina Pedreschi; Claudia Fuentealba (Horticulturae, 2023)
Sweet cherry may develop surface pitting during prolonged cold storage, and susceptibility among varieties is related to metabolites in response to cold and mechanical damage. This study aimed to evaluate the metabolic changes in sweet cherry fruits subjected to melatonin treatment and induced surface pitting. Melatonin (400 µM) was applied to sweet cherries before pitting induction and then stored at 1 °C for 20 d. Melatonin treatment attenuated the severity of pitting damage during cold storage, with an average severity value of 3.1 for cherries with melatonin and 2.6 without melatonin. In addition, melatonin application appeared to modulate metabolic responses due to the regulation of metabolic pathways related to abiotic stress. Upregulation of different secondary metabolites was observed after 16 h of melatonin treatment and cold storage. Moreover, some metabolites of the sphingolipid and sulfur metabolism were upregulated after 10 d. This research is the first to show that melatonin may influence the response of sweet cherries to cold and mechanical damage.